PEMANFAATAN BUAH MAHONI SEBAGAI TEH PENURUN BERAT BADAN (DIET) - Sipahutar, Amlisa Mutiandini; Sipahutar, May Sintia; Ardiansyah, M. Edo; Amsal, Azhar (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2023)
Mahogany seeds contain bioactive compounds such as alkaloids, steroids, saponins, and flavonoids. Flavonoids are useful for reducing fat deposits and cholesterol levels in the blood vessels, while saponins are useful for preventing fat accumulation, improving blood sugar levels, helping increase the immune system. Many people experience unhealthy lifestyle changes, caused by excessive consumption of high-cholesterol foods, irregular eating patterns, and low consumption of fruits and vegetables, which have the potential to cause obesity/obesity. In this study, using mahogany fruit as a weight loss tea (diet). This study applies research with a quantitative approach. The type of research used is experimental. The sample measurement uses the BMI (Body Mass Index) system where to measure the body mass index it can be measured by weight (Kilograms) and height (meters) of the sample. In this study, a sample of UIN ArRaniry students aged around 21 years was used. The results of consuming diet tea for 3 consecutive weeks experienced a weight loss of approximately 1 kilogram per week. Where diet tea is drunk 2 times a day, in the morning and evening. Diet tea is brewed by taking ½ tablespoon of diet tea and brewing it with 200 ml of warm water. The results showed that mahogany seeds processed into tea were effective in losing weight after being consumed for 3 weeks in a row with a decrease of approximately 1 kilogram per day. week, because the mahogany seeds contain bioactive compounds such as alkaloids, steroids, saponins, and flavonoids. Flavonoids are useful for reducing fat deposits and cholesterol levels in the blood vessels. While saponins are useful for preventing fat accumulation, improving blood sugar levels, helping increase the immune system, and slowing the blood clotting process.